Trends of oral cancer in University College Hospital, Ibadan, Nigeria (Nigerian Dental Journal, 2010)
Objective: The aim of this study was to describe the trend and recent pattern of oral cancer in the University College Hospital, Ibadan, Nigeria.Method: A retrospective analysis of all cases of oral cancer (excluding lymphoid cancers) documented in the records of the Departments of Oral and Maxillofacial Surgery and Pathology, University College Hospital (UCH), Ibadan, from the year 1983 to 2007 was done. The analysis of the data collected was compared with three earlier studies in this same centre and the published literature in general.Result: Over the 25-year-period a total 450 cases of oral cancer were recorded. More than half of the cases were squamous cell carcinomas (SCC) and 58.0% of these occurred in the palate which was the commonest site. Compared with previous studies, the male to female ratio of 1.4:1 revealed a higher number of females, and more patients were recorded in the first and tenth decades of life.Conclusion: The trends in oral cancer prevalence in UCH, Ibadan, show that oral SCC, still occurs commonly in the palate in our environment, and constituted the bulk of oral cancer. In addition, more females and patients within the extremes of age are being increasingly affected. There is before a need for more investigations into the possible aetiological factors in our environment in order to offer a preventive approach to the management of the disease.
Keywords: Oral cavity; Sarcomas; Squamous cell carcinoma; Ibadan